Obligation and liability of the carrier under the Rotterdam Rules: An appraisal - Kyaw, Hla Win (2015)
At the international level, conventions on the contracts for the carriage of goods by sea were gradually developed and four major legal regimes have been emerged, namely, the International Convention for the Unification of Certain Rules of Law relating to Bills of Lading 1924 (the Hague Rules); the Hague Rules as Amended by the Brussels Protocol 1968 (the Hague-Visby Rules); the United Nations Convention on the Carriage of Goods by Sea 1978 (the Hamburg Rules); and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 (the Rotterdam Rules).There were concerns over lack of uniformity among the previous legal regimes governing the international carriage of goods by sea, i.e., the Hague Rules, the Hague-Visby Rules and the Hamburg Rules.There was also no universal regime to govern contracts of carriage involving various modes of transport in connection with contracts of carriage by sea. In addition, they do not provide any legal basis for modern transport practices such as containerisation, the use of electronic transport documents and door-to-door transport contracts (see the Preamble of the Rotterdam Rules).